Acceptorless dehydrogenative synthesis of primary amides from alcohols and ammonia. Issue 13 (16th March 2022) - Luo, Jie; Zhou, Quan-Quan; Montag, Michael; Ben-David, Yehoshoa; Milstein, David
Abstract : An efficient and selective synthesis of primary amides from alcohols and ammonia, with H2 evolution, has been achieved by an unprecedented acceptorless dehydrogenative process catalyzed by a pyridine-based PNN–ruthenium pincer complex. Abstract : The highly desirable synthesis of the widely-used primary amides directly from alcohols and ammonia via acceptorless dehydrogenative coupling represents a clean, atom-economical, sustainable process. Nevertheless, such a reaction has not been previously reported, and the existing catalytic systems instead generate other N-containing products, e.g., amines, imines and nitriles. Herein, we demonstrate an efficient and selective ruthenium-catalyzed synthesis of primary amides from alcohols and ammonia gas, accompanied by H2 liberation. Various aliphatic and aromatic primary amides were synthesized in high yields, with no observable N-containing byproducts. The selectivity of this system toward primary amide formation is rationalized through density functional theory (DFT) calculations, which show that dehydrogenation of the hemiaminal intermediate into primary amide is energetically favored over its dehydration into imine.